The Multitask Theory of State Enterprise Reform: Empirical Evidence from China - Bai, Chong-En; Lu, Jiangyong; Tao, Zhigang (American Economic Review, 2006)
The Multitask Theory of State Enterprise Reform: Empirical Evidence from China by Chong-En Bai, Jiangyong Lu and Zhigang Tao. Published in volume 96, issue 2, pages 353-357 of American Economic Review, May 2006